2005
DOI: 10.1073/pnas.0501684102
|View full text |Cite
|
Sign up to set email alerts
|

Attentional integration between anatomically distinct stimulus representations in early visual cortex

Abstract: Vision often requires attending to, and integrating information from, distant parts of the visual field. However, the neural basis for such long-range integration is not clearly understood. Here, we demonstrate a specific neural signature of attentional integration between stimuli in different parts of the visual field. Using functional MRI, we found that a task requiring the integration of information between two attended but spatially separated stimuli actively modulated the degree of functional integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 58 publications
6
33
0
Order By: Relevance
“…Whereas it was possible to decode with marginal significance whether subjects were preparing for the color or the motion task (classification performance, 61%; P = 0.058; permutation test), we were not able to predict the task performance (classification performance color task, 44%; motion task, 55%; all P values >0.2). Similar dissociations between mean response amplitude and connectivity have been previously reported in other cognitive domains (15,17,19). Thus, it appears unlikely that the observed topological changes can be explained by differences in BOLD amplitude.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Whereas it was possible to decode with marginal significance whether subjects were preparing for the color or the motion task (classification performance, 61%; P = 0.058; permutation test), we were not able to predict the task performance (classification performance color task, 44%; motion task, 55%; all P values >0.2). Similar dissociations between mean response amplitude and connectivity have been previously reported in other cognitive domains (15,17,19). Thus, it appears unlikely that the observed topological changes can be explained by differences in BOLD amplitude.…”
Section: Resultssupporting
confidence: 64%
“…It has been shown that attention can modulate interarea correlations between distant cortical regions, independent from changes in regional blood flow (17)(18)(19). However, these studies were usually limited to a small selection of cortical regions (2,7,15,(18)(19)(20).…”
mentioning
confidence: 99%
“…In humans, shifts in the baseline activity of primary visual cortex in the absence of any visual stimulation have been observed (Kastner et al, 1999;Haynes et al, 2005;Silver et al, 2007). This activity is sustained during the time delay preceding stimulus onset, is associated with the deployment of covert spatial attention, and regulated by parietal structures (Chawla et al, 1999;Haynes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This activity is sustained during the time delay preceding stimulus onset, is associated with the deployment of covert spatial attention, and regulated by parietal structures (Chawla et al, 1999;Haynes et al, 2005). In the present study we did not explicitly manipulate spatial attention (i.e., spatial expectancy) but instead required participants to focus on temporal expectation.…”
Section: Discussionmentioning
confidence: 99%
“…Orban et al (2004) proposed a distinction of three hierarchical levels of integrational complexity in the primate visual cortex, which also correspond to different amounts of certainty regarding the homology between different primate species including humans. For early visual areas (V1, V2, V3), anatomical and functional homology between humans and nonhuman primates can be considered as largely proven (Conway and Tsao, 2006;Foster et al, 1985;Gallant et al, 1998;Haynes et al, 2005, but see Rosa and Manger, 2005). For midlevel visual areas (V3A, V4, MT) there is strong evidence for a largely preserved regional homology of their structural and functional organization (Hasnain et al, 1998;Larsson et al, 2006;Merriam and Colby, 2005).…”
Section: Introductionmentioning
confidence: 96%